2008
DOI: 10.1097/ico.0b013e318165d110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Topography With Orbscan II in First-degree Relatives of Patients With Keratoconus

Abstract: The keratoconus incidence was found to be 11% in first-degree relatives of patients with keratoconus as opposed to a reported incidence of keratoconus of 0.05% in the general population. In first-degree relatives of patients with keratoconus who did not have a topographic keratoconus pattern, abnormal corneal topographic values were detected. The asymptomatic relatives of patients with keratoconus should undergo a thorough preoperative analysis for subtle topographic abnormalities before any keratorefractive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 14 publications
2
28
1
Order By: Relevance
“…17 Topography in firstdegree relatives of keratoconus patients is also more likely to show patterns resembling keratoconus. 18 Ioti et al 19 found keratoconus or keratoconus suspect patterns in 60.2% of family members of Japanese keratoconus patients by topography and/ or Orbscan. Wang et al 20 in a segregation analysis of corneal topography comparing affected keratoconus patients, their relatives, and unaffected controls found that a major gene model, most consistent with recessive transmission, best fit their data although sporadic and environmental models were not supported.…”
mentioning
confidence: 97%
“…17 Topography in firstdegree relatives of keratoconus patients is also more likely to show patterns resembling keratoconus. 18 Ioti et al 19 found keratoconus or keratoconus suspect patterns in 60.2% of family members of Japanese keratoconus patients by topography and/ or Orbscan. Wang et al 20 in a segregation analysis of corneal topography comparing affected keratoconus patients, their relatives, and unaffected controls found that a major gene model, most consistent with recessive transmission, best fit their data although sporadic and environmental models were not supported.…”
mentioning
confidence: 97%
“…1,2 This idiopathic corneal dystrophy is characterized by progressive bulging and thinning of the stromal layer of the cornea, so-called corneal ectasia.…”
mentioning
confidence: 99%
“…Several parameters to help the physician conclude that an eye is normal or abnormal have been suggested. 15,[26][27][28][29][30][31][32][33][34][35][36][37][38] Keratoconus progression in the fellow eye of the patient who has keratoconus can help us understand the characteristics of the early keratoconic eye. However, even with corneal curvature and thickness measurements, it is difficult to differentiate the fellow eye of a patient with keratoconus from a normal eye.…”
Section: Detection Of Eyes That May Progress To Ectasia Naturallymentioning
confidence: 99%